Appreciation of poetry in indonesian subjects Through songs to increase student ability at the Fifth grade students at sd negeri 10 koto jua - Leni Marlina (Jurnal Ilmiah Pendidikan Scholastic, 2017)
In the Indonesian Language Lesson (GBPP) signs relating to literary teaching it is mentioned that (1) Language learning needs to pay attention to the principles of teaching, among others, which are easier than those things that are close to distant, from simple to complex , From the know to the unknown, from the concrete to the abstract, (2) The literary learningis intended to enhance the students' ability to appreciate literature closely related to the practice of sharpening feelings, reasoning and imagination, and sensitivity to society, culture and environment , And (3) The selection of literary material is associated with the theme. If teachers have difficulty in getting the material according to the chosen theme then the learning materials sasrta may not be in accordance with the theme presented. This is related to the purpose of class V, ie students are able to read literary works with pengahayatan and understand the various ways of expressing feelings and ideas in the literary work. The learning of poetry appreciation that is taught in SDN 10 Koto Jua starts class I, is one of sasrta learning material that is more difficult and causes more problems than the appreciation of other literary works (Prosa) Learning poetry appreciation that should be very fun even become boring specter And frightening, both for teachers and students, Teachers who tend to teach the appreciation of poems in bits and pieces, with materials that are adapted to the level of kirang student development and using an approach that is not dipdukan with empathy aspects of language skills (listening, speaking and writing) Will cause the students unconditioned learning poetic appreciation.